Efeitos do uso de analgesia durante o parto vaginal no assoalho pélvico: coorte prospectivo - Almeida, Maria Evilene Macena de (2023)
The objective is to verify the association between the use of analgesia in vaginal delivery and the prevalence of incontinence complaints up to six months postpartum. This is a prospective cohort, its writing followed in the footsteps of the STROBE initiative. Held in the rooming-in of a maternity school in the state of Ceará. Primiparous vaginal delivery at term in cephalic presentation and over 18 years old were included. Those with complaints of urinary or anal incontinence before childbirth were excluded. Participants were divided into two groups: Analgesia Group (AG) and Non-Analgesia Group (NAG). The total collection period was from March 2022 to August 2023. The sample calculation estimated the need to evaluate 50 exposed and 150 unexposed women. Patient recruitment took place between March 2022 and February 2023, in which questionnaires and scales were applied, in addition to collection from medical records. Contact information was also requested for follow-up at 3 and 6 months after delivery. Data were tabulated in Microsoft Excel and analyzed in SPSS v20.0. Research approved under opinion number 5,261,767 and CAAE 55620722.8.0000.5050. A total of 159 primiparous women were recruited, of which 63 reported UI and AI complaints. 96 patients were followed in the research, 73 in the NAG and 23 in the AG. The AG had higher percentages of instrumental deliveries (p<0.05), with greater varieties of fetal head position in posterior and transverse cephalic pole detachment (p = 0.027) and prolonged duration of the second stage of labor (p = 0.001). Furthermore, when together, third- and fourth-degree lacerations occurred in a greater proportion in the AG (p = 0.032). At 3 months after delivery, the incidence of UI and AI was similar in both groups (p = 0.491 and p = 1.00), with regard to types, SUI and loss of flatus were the most prevalent. There was no difference between the UDI-6 and CRADI-8 subscale scores. The impact of PFD symptoms on quality of life was similar. At 6 months after delivery, the prevalence of UI and AI were similar (p = 0.742 and p = 1.00) the most prevalent type of UI continued to be SUI, as well as the most prevalent AI, loss of flatus. No difference was observed between the groups, in the scores of the subscales UDI-6 and CRADI-8 and of the scale PFDI-20. As for the impact of PFD symptoms on quality of life, no difference was observed either. In this study, no association was found between the use of analgesia and the prevalence of incontinence complaints during the postpartum period. The incidence of UI and AI complaints were similar in both groups. There was no difference in the scores of the assessment scales of the impact of PFD symptoms on the pelvic floor and in the women's quality of life during the follow-up of up to six months after childbirth. Despite this, other variables were observed that were associated with the use of labor analgesia that deserve attention.